A consensus on stomal, parastomal and peristomal complications - Keryln Carville, & Emily Haesler, & Tania Norman, & Pat Walls and & Leanne Monterosso (WCET Journal - Portuguese Edition, 2022)
Aim To establish a consensus on terminology used to define stomal, parastomal and peristomal complications in Australia. Methods A list of stomal, parastomal and peristomal complications was generated through group dialogue which was informed by the clinical and academic knowledge of the researchers. An extensive literature review was undertaken to identify any additional terms and to create a database of definitions/descriptions. A library of images related to the identified conditions was generated. An online Delphi process was conducted amongst a representative, purposive sample of Australia expert wound, ostomy, continence nurses (WOCNs) and colorectal surgeons. Ten terms were presented to the panel with descriptive photographs of each complication. Up to three Delphi rounds, and if necessary a priority voting round, were conducted. Results Seven of the ten terms reached agreement in the first round. One term (allergic dermatitis) was refined (allergic contact dermatitis) and reached agreement in the second round. Two terms (mucocutaneous granuloma and mucosal granuloma) were considered by the panel to be the same condition in different anatomical locations and were combined as one term (granuloma). Two terms (skin stripping and tension blisters) were combined as one term – medical adhesive related skin injury (MARSI) – and reached agreement in round two. Conclusion A consensus in terminology used to describe stomal, para/peristomal complications will enhance communication amongst patients and health professionals, and advance opportunities for education and benchmarking of stomal, para and peristomal complications nationally.